Media framing on 2018 general election : a comparative content analysis on newspapers coverage toward political parties in Malaysia - Ainis Azreen Rosli,; Mohd Azizuddin Mohd Sani, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article explores the mainstream media favorability towards political parties in the context of newspaper coverage in Malaysia during the 14th general election in 2018 (GE-14). The newspapers selected for this study are three Malay, two English, two Mandarin and two Tamil newspapers namely: 'Utusan Malaysia,' 'Berita Harian', 'Sinar Harian', 'New Straits Times', 'The Star', 'Nanyang Siang Pau', 'Sin Chew Daily', 'Nanban' and 'Osai'. The background of the newspapers was explored in order to understand the ownerships and approaches in covering the news about GE-14. This study was carried out in two separate phases, in which the data were derived from both periods before and after the GE-14. The data were classified into few categories based on reports on Barisan Nasional (BN), Pakatan Harapan (PH), Gagasan Sejahtera (GS) through the frequencies and percentages of the positive, negative, and neutral forms of coverage. The result of this study implies that in 2018, most of the mainstream media reporting was pro-government, which attributed to the linkage to political parties. Surprisingly, the unprecedented victory of the opposition can be seen to relate to the growth of positive coverage towards Pakatan Harapan, subsequently after the general election. Through content analysis of these selected newspapers, the author discussed gender-related coverage and general issues during the chosen period of the study.